Evaluation of biofilm formation on different clear orthodontic retainer materials - Suhad M Hamdoon; Saeed AlSamak; Mahmood Kh Ahmed; Saad Gasgoos (Wolters Kluwer Medknow Publications, 2022)
Aim: To assess the chemical composition and oral biofilm formation on different types of commercially available clear orthodontic retainer materials (CORM). Materials and Methods: Four types of CORM commercially available were used (Clear advantage series I (CAS1), Clear advantage series II (CAS2), Endure (ES), and CENTRI FORM-clear rigid material (CFCRM)). Circular samples (12 mm diameter) of each CORM were prepared for (n = 40). Unstimulated saliva from twenty volunteers was collected. Fourier Transformation Infrared Spectroscopy (FTIR) was used for the evaluation of the chemical composition of CORM. For the quantitative assessment of oral biofilm formation, samples of each CORM were incubated for twenty-four hours, and crystal violet assay (CVA) was utilized. The degree of absorbance was measured using a spectrophotometer at 570 nm. For qualitative evaluation of oral formation, the samples of each CORM were incubated for 24 hours, and viable biofilm cells stained by acridine orange were examined under a fluorescent microscope. Results: FTIR findings showed that CAS2 was made of polypropylene and ES is made of polyvinyl chloride, while others were made of co-polyester. CVA results confirmed that CAS2 showed the lowest biofilm formation, which differs significantly compared to CAS1, CFCRM, and ES. No significant difference in biofilm formation was detected between CAS1, CFCRM, and ES. Viable biofilm cells staining by acridine orange showed that CAS2 demonstrated smaller microcolonies of viable biofilm cells compared with CAS1, CFCRM, and ES, which confirmed the result obtained by CVA. Conclusions: CAS2 showed anti-microbial activities with a decrease the in vitro biofilm formation, which may be related to its chemical composition.